IMMU-11. LOCOREGIONAL DELIVERY OF TRANSIENT GD2 CAR T CELLS FOR SAFE AND EFFECTIVE TREATMENT OF DIPG. (4th December 2020) - Foster, Jessica; Griffin, Crystal; Stern, Allison; Brimley, Cameron; Smith, Tiffany; Storm, Phillip; Resnick, Adam
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a universally fatal pediatric brain tumor with a median survival of one year. Recently Mount et al (Nat Med 2018) discovered the disialoganglioside GD2 is present at high levels on the surface of DIPG and can be targeted using GD2-directed CAR T cells. However, permanently expressed CAR T cells created by lentiviral transduction resulted in a significant number of deaths from tumor swelling with uncontrolled T cell proliferation. We hypothesized that using mRNA to create transient GD2-directed CAR T cells delivered locally with repeated dosing would result in a safer yet equally effective way to treat DIPG using CAR T cell therapy. In vitro studies using mRNA GD2-directed CAR T cells resulted in robust tumor cytotoxicity and T cell degranulation across a panel of six DIPG cell lines. Using an orthotopic murine model of SU-DIPGXIIIP*, an extremely aggressive model, we delivered of a single dose of two million mRNA GD2-directed CAR T cells locoregionally to the pons via stereotactic injection. The mRNA GD2-directed CAR T cells resulted in no toxic deaths of the mice. In addition, a single dose of mRNA CAR T cells targeting GD2 prolonged survival of the mice by a median of six days (p<0.05). Ongoing studies using an indwelling catheter for repeated dosing of mRNA CAR T cells are currently underway and results expected at the time of presentation. This work will form of the basis of an mRNA CAR T cell trial targeting GD2 for patients with DIPG.